Virulence of invasive Salmonella Typhimurium ST313 in animal models of infection. - Girish Ramachandran; Aruna Panda; Ellen E Higginson; Eugene Ateh; Michael M Lipsky; Sunil Sen; Courtney A Matson; Jasnehta Permala-Booth; Louis J DeTolla; Sharon M Tennant (PLOS Neglected Tropical Diseases, 2017)
Salmonella Typhimurium sequence type (ST) 313 produces septicemia in infants in sub-Saharan Africa. Although there are known genetic and phenotypic differences between ST313 strains and gastroenteritis-associated ST19 strains, conflicting data about the in vivo virulence of ST313 strains have been reported. To resolve these differences, we tested clinical Salmonella Typhimurium ST313 and ST19 strains in murine and rhesus macaque infection models. The 50% lethal dose (LD50) was determined for three Salmonella Typhimurium ST19 and ST313 strains in mice. For dissemination studies, bacterial burden in organs was determined at various time-points post-challenge. Indian rhesus macaques were infected with one ST19 and one ST313 strain. Animals were monitored for clinical signs and bacterial burden and pathology were determined. The LD50 values for ST19 and ST313 infected mice were not significantly different. However, ST313-infected BALB/c mice had significantly higher bacterial numbers in blood at 24 h than ST19-infected mice. ST19-infected rhesus macaques exhibited moderate-to-severe diarrhea while ST313-infected monkeys showed no-to-mild diarrhea. ST19-infected monkeys had higher bacterial burden and increased inflammation in tissues. Our data suggest that Salmonella Typhimurium ST313 invasiveness may be investigated using mice. The non-human primate results are consistent with clinical data, suggesting that ST313 strains do not cause diarrhea.